Document design - Jansen, Carel; Maes, Alfons (SA journal of linguistics = SA tydskrif vir taalkunde, 1999)
This article focuses on a fairly new discipline in the field of language & communication studies: document design. Document design is defined as the field of theory & practice aimed at creating comprehensible, persuasive, & usable functional documents. The article discusses both its social & its academic mission. On the one hand, document design intends to meet the communicative needs of individuals & organizations in modern society; on the other, it fits in with a new view on language training & text research which is characterized by a close connection between theory & practice & a high degree of interdisciplinarity & social relevance. After an introductory first section, the second section briefly motivates why document design professionals are needed. In the third section, the social relevance of document design research is argued for & illustrated by describing the set up & results of one of the earlier Dutch studies into the effectiveness of government forms. The fourth section surveys the different types of knowledge & expertise a document design expert is expected to display. The fifth section goes into the academic training of document design professionals, addressing how document design training at an academic level should be organized so as to achieve both its academic & social missions. The sixth section illustrates how document design gradually takes its place as an interdisciplinary scientific discipline with its specific research goals & methods. 4 Figures, 55 References. Adapted from the source document